Odpowiedzi

2010-02-28T19:58:59+01:00
(d1/2)^2 + (d2/2)^2 = a^2
(x/2)^2+(x+6/2)^2=(2 pierw 10)^2
x^2/4 + (x^2+12x+36)/4=40
x^2+x^2+12x+36=160
2x^2+12x-124=0
x^2+6x-62=0

delta = 36+248=284
pierw delta = 2 piew 71

x=(-6+2 pierw 71)/2 = -3 + 2 pierw 71

2010-02-28T20:22:03+01:00
Nie wiem ja to tak liczyłam:

(x+6/2)²+(x/2)²=(2√10)²
x²+12x+36/4+x²/4=40/×4
x²+12x+36+x²=160
2x²+12x-124=0
Δ=144+992=1136
√Δ=4√71
x1=-12-4√71/4=4(-3-√71)/4=-3-√71
x2=-12+4√71/4=4(-3+√71)/4=-3+√71
mi tak wyszło ale nie wiem czy dobrze zrobiłam :/
ale starałam się